2021
DOI: 10.1111/edt.12647
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of teeth in mandibular fracture lines

Abstract: Background/Aims Teeth in a jaw fracture line, because of the presence of the periodontal ligament, may communicate with the oral cavity. There are no guidelines for the management of teeth in mandibular fracture lines. The aim of this study was to investigate the factors related to dental problems with teeth involved in mandibular fracture lines and to determine the best treatment option. Material and Methods This retrospective study was based on the medical and radiographic records of patients with mandibular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Even with preservation, various other progressions of complications were reviewed and might happen during the follow-up. 19 Interestingly, in a research report offered by Neal et al, 20 the rate of complications came to 16.1% in patients who underwent initial extractions without trying to preservative, whereas the complication rate of the teeth preserved was 13.7%, which showed no much difference in preservation of affected tooth if the decision were seriously concerned. Even though there seems to be a different result compared with us, we still got a significantly lower (5.12%) complication rate compared with the previous reports.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Even with preservation, various other progressions of complications were reviewed and might happen during the follow-up. 19 Interestingly, in a research report offered by Neal et al, 20 the rate of complications came to 16.1% in patients who underwent initial extractions without trying to preservative, whereas the complication rate of the teeth preserved was 13.7%, which showed no much difference in preservation of affected tooth if the decision were seriously concerned. Even though there seems to be a different result compared with us, we still got a significantly lower (5.12%) complication rate compared with the previous reports.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to our results, in the retrospective study reported by Lee and colleagues, if the prophylactic extractions of teeth were carried out to those in the fracture lines, the evaluation of the follow-up revealed a lower incidence of complications compared with those who were left in place. Even with preservation, various other progressions of complications were reviewed and might happen during the follow-up 19 . Interestingly, in a research report offered by Neal et al, 20 the rate of complications came to 16.1% in patients who underwent initial extractions without trying to preservative, whereas the complication rate of the teeth preserved was 13.7%, which showed no much difference in preservation of affected tooth if the decision were seriously concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in the occurrence of dental problems were observed in teeth with a bony displacement exceeding 3 mm. The location of the fracture line in relation to the tooth apex seems not to affect the occurrence of dental problems [ 21 ].…”
Section: Discussionmentioning
confidence: 99%